Growth mechanism of Pb0.9Cd0.1Te: Pb thin films prepared by PVD technique - Tetiana Mazur; Bohdana Naidych; Rostyslav Yavorskyi; Oksana Holovata; Taras Parashchuk; Oksana Zamurujeva; Orest Voznyak; Lyubomyr Nykyruy (Nano Express)
The complex surface morphology, defect subsystem and an ab initio model study of Pb _1-x Cd _x Te thin films deposited on mica-muscovite substrates by PVD technology are presented in this paper. The thickness, growth mechanisms and uniformity of condensates dependence on deposition regimes were studied by scanning electron microscopy and energy-dispersive x-ray spectroscopy. The deposited films have a granular structure and sizes of crystallites depend on thickness and difference between substrate and condensate crystallographic parameters. The dominance of film growth by the Vollmer-Weber mechanism is demonstrate. Studies of film growth mechanisms allowed us to predict that the formation of grains and the dynamics of their size changes during film growth are caused by complex defects that are associated with Cd atoms in nodes and vacancies of chalcogens.